WUSCHEL-related homeobox gene WOX11 increases rice drought resistance by controlling root hair formation and root system development. (1st February 2016) - Cheng, Saifeng; Zhou, Dao-Xiu; Zhao, Yu
ABSTRACT: Roots are essential organs for anchoring plants, exploring and exploiting soil resources, and establishing plant-microorganisms communities in vascular plants. Rice has a complex root system architecture consisting of several root types, including primary roots, lateral roots, and crown roots. Crown roots constitute the major part of the rice root system and play important roles during the growing period. Recently, we have refined a mechanism that involves ERF3/WOX11 interaction is required to regulate the expression of genes in the cytokinin signaling pathway during the different stages of crown roots development in rice. In this study, we further analyzed the root phenotypes of WOX11 transgenic plants and revealed that WOX11 also acts in controlling root hair development and enhancing rice drought resistance, in addition to its roles in regulating crown root and lateral root development. Based on this new finding, we proposed the mechanism of that WOX11 is involved in drought resistance by modulating rice root system development.